New technologies in vascular surgery: San Donato's experience in the last decades. (29th April 2016) - Mazzaccaro, Daniela; Occhiuto, Maria Teresa; Stegher, Silvia; Righini, Paolo; Malacrida, Giovanni; Nano, Giovanni
Abstract: The Department of Vascular Surgery I at IRCCS Policlinico San Donato has been part of the Cardiovascular Center "Edmondo Malan" since the end of the 1980s. Surgical activity of the Department has always been designed to prevent and treat vascular diseases such as aneurysms of the thoracic and abdominal aorta and peripheral vessels, carotid artery stenosis, peripheral arterial disease, and chronic venous insufficiency. Excellent results have been achieved with the endovascular treatment of both symptomatic and asymptomatic carotid artery stenosis also by using innovative devices. Another point of interest regards the endovascular treatment of more complex thoraco-abdominal aortic aneurysms. We report our experience in the last decades.